Hubungan Asupan Kalium dengan Hipertensi pada Perempuan Etnis Minangkabau - Usfa, Marwanda Da; Hasni, Dita; Birman, Yuliza; Febrianto, Budi Yulhasfi (Universitas Muhammadiyah Semarang, 2023)
Background : Hypertension is a blood pressure disease, where there is an increase in systolic (≥140 mmHg) and/or diastolic (≥ 90 mmHg) blood pressure quickly or slowly. Objective : This study aims to determine the relationship between potassium intake and the incidence of hypertension in inangkabau ethnic women. Methods : This research is a type of analytical research with a case control research design. The population in this study were all Minangkabau ethnic women who suffered from hypertension who went to the Air Padang Children's Health Center, with 114 samples that met the inclusion and exclusion criteria. Bivariate and univariate data analysis is presented in the form of frequency distribution and percentage, and the data is processed using the SPSS program. Result : This study showed that as many as 112 people (98.2%) of Minangkabau ethnic women with less potassium intake, and 2 people (1.8%) with adequate potassium intake. The average potassium intake in the hypertensive women group was 855.0146 mg, while the nonhypertensive women group was 1699.5777 mg. Hypertensive women have an average systolic blood pressure of 151.44, while a diastolic blood pressure of 92.09. Women without hypertension had an average systolic blood pressure of 111.49, while a diastolic blood pressure of 76.93. Less potassium intake was found in the hypertensive women group, namely 57 people (100%) compared to the nonhypertensive women group, namely 55 people (96.5%). Conclusion : There is no significant relationship between potassium intake and blood pressure in Minangkabau ethnic women. Keywords: Hypertension, Potassium, Minangkabau